Prevalensi Infeksi Clostridium difficile Pada Pasien Neutropenia dengan Kanker - Andree Kurniawan (Fakultas Kedokteran Universitas Pelita Harapan, 2018)
Clostridium difficile (C. difficile) infection mostly found in immunocompromised patient. Most of the patients with neutropenia had hematologic malignancy and come with multiple risk factors for C. difficile infection. The aim of this study is to know the prevalence and characteristic of C. difficile infections in cancer neutropenia patients. This cross-sectional study was done in secondary referral hospital in suburban Karawaci, Tangerang, Banten, Indonesia from June 2014 until Mei 2015. Adult cancer patients hospitalized with neutrophil count less than 1500 106 cell/L were included. All patients were checked for antigen and toxin C. difficile in faeces. From 25 patients were evaluated for C. difficile infection in neutropenia. C. difficile antigen only found in one patient or 4% sample.Key words: C. difficile, cancer, neutropenia